2022
DOI: 10.3390/ijms232214385
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of BRAF-MAPK and STAT3 Signaling Pathways in Resveratrol-Suppressed Anaplastic Thyroid Cancer Cells with BRAF Mutations

Abstract: Anaplastic thyroid cancer is an extremely lethal malignancy without reliable treatment. BRAFV600E point mutation is common in ATCs, which leads to MAPK signaling activation and is regarded as a therapeutic target. Resveratrol inhibits ATC cell growth, while its impact on BRAF-MAPK signaling remains unknown. This study aims to address this issue by elucidating the statuses of BRAF-MAPK and STAT3 signaling activities in resveratrol-treated THJ-11T, THJ-16T, and THJ-21T ATC cells and Nthyori 3-1 thyroid epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The MAPK and AKT/mTOR signaling cascades are found to be the key ones in autophagy [ 63 ]. PIK3CA, the initial component of the AKT/mTOR cascade [ 64 ]. CCDC6, protein 6 containing an antenna domain, interacts with CREB1 (reaction element binding protein cAMP 1) and suppresses its transcriptional activity [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPK and AKT/mTOR signaling cascades are found to be the key ones in autophagy [ 63 ]. PIK3CA, the initial component of the AKT/mTOR cascade [ 64 ]. CCDC6, protein 6 containing an antenna domain, interacts with CREB1 (reaction element binding protein cAMP 1) and suppresses its transcriptional activity [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…MAPK1 and MAPK3 are the components of the rout that orchestrate the rapid cancer cell division and determine the aggressive cancer cells behavior [ 63 ]. PIK3CA activates AKT/mTOR signaling and operates the protein’s metabolism as a key mechanism of cells adaptation and survival [ 64 ]. The novel genetic marker is CCDC6, the components of the gene’s translocation in PTC [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The method used in the double staining assay was conducted as previously described. 36,37 Triton X-100 detergent (0.1%) was used as a positive control. Calcein AM and PI dye were added for 30 min.…”
Section: Calcein Am/propidium Iodide (Pi) Double Staining Assaymentioning
confidence: 99%
“…The combination therapy of dabrafenib, an FDA-approved BRAF inhibitor, and trametinib, a MEK inhibitor, against BRAF V600E -mutated ATC ( Subbiah et al, 2020 ), can extend survival to 12 months in 12 percent of patients ( Subbiah et al, 2018 ). In contrast, resveratrol has a more potent anti-ATC effect compared to BRAF-MAPK-targeted drugs (dabrafenib and trametinib) by simultaneously inhibiting the BRAF-MAPK and STAT3 signaling pathways in ATC cell lines with BRAF fusion or point mutation ( Lu et al, 2022 ). The activation of JAK2/STAT3 is thought to be a significant factor contributing to cancer cell resistance towards drugs targeting the MAPK pathway ( Crispo et al, 2019 ).…”
Section: Promising Natural Products For the Treatment Of Thyroid Cancermentioning
confidence: 99%
“…In in vitro and in vivo studies of thyroid cancer, NPs have shown good therapeutic potential. Numerous studies have demonstrated that various natural compounds derived from food and herbs possess the ability to inhibit TC, including inhibiting the occurrence and development of TC ( Yu et al, 2013 ; Hong et al, 2021 ; Lu et al, 2022 ), promoting redifferentiation of poorly differentiated TC ( Lakshmanan et al, 2015 ; Zhang L. et al, 2021b ), alleviating TC drug treatment resistance ( Li et al, 2018 ; Bian et al, 2020 ; Celano et al, 2020 ), and so on. Previously, my research group published basic research on tangeretin and nobiletin.…”
Section: Introductionmentioning
confidence: 99%